Students with Special Needs and Their Parents – Informal Participation of a Parent in the Education of an Adult Child - Pyrczak-Piega, Monika; Kutek-Sładek, Katarzyna (Central European Journal of Educational Research, 2023)
The article presents the issue of participation of adult students’ parents in their academic life. There are many examples in the literature of how important is the support of students’ with disabilities parents at the universites. This determines academic success. Disability (its depth, type, cause, limitations resulting from it) is a determining factor for independence, and consequently for the parent’s participation in the student’s academic life. The parent’s attitude towards their own child’s disability is also related to the parent’s participation in the study. The main questions of presented research is: how do students, parents and university staff see the participation of parents in their adult chilredn higher education? This study was qualitative in nature and the individual in-depth interviews were conducted in the course of the study. Two female students with disabilities and their mothers, as well as a member of staff from the one of Polish university’s disability office, were invited to participate in the study. The results show that students, parents and university’s staff can present different opinions about parental suport. The fact is that parental participation cannot be permanent. Each time this type of support should be considered on an individual basis, with particular regard to the welfare of the the student. The results of the survey are relevant to the university’s process of planning support for students with disabilities so as to work with parents with the students’ consent.